Cross-country librarying: Teaching information literacy at HVL - Austrheim, Gunhild (Septentrio Conference Series, 2020)
Since 2012 all students in higher education in Norway have had learning outcomes related to finding, evaluating and using information in their study work. All degree programmes have these learning outcomes in their study plans and all library teachings in information literacy are related to these learning outcomes. HVL is the result of a merger between three institutions, all with libraries, and librarians that teach. The study portfolio of the former institutions were quite similar, nonetheless, it turned out our library teaching offers varied from one degree programme to the next, and from one campus to the next. We needed to unify our practices across the institution. How could we achieve this across geography, tradition and work cultures? We have worked on the content of our teaching, the competency of our staff and our methods of collaboration with faculty, hoping that taken together this will be a magic mixture for our students’ information literacy.